2017
DOI: 10.1523/eneuro.0117-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Additive Neurorestorative Effect of Simultaneously Administered CDNF and GDNF in Hemiparkinsonian Rats: Implications for Different Mechanism of Action

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder associated with a progressive loss of dopaminergic (DAergic) neurons of the substantia nigra (SN) and the accumulation of intracellular inclusions containing α-synuclein. Current therapies do not stop the progression of the disease, and the efficacy of these treatments wanes over time. Neurotrophic factors (NTFs) are naturally occurring proteins promoting the survival and differentiation of neurons and the maintenance of neuronal contacts. CDNF (cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Another interesting finding is that there is likely a reciprocal regulation between p58 IPK and MANF in retinal cells undergoing ER stress. Recent studies show that MANF protects CNS neurons (Voutilainen et al, 2017 ) and markedly improves RGC survival in a rat glaucoma model (Gao et al, 2017 ). Our data support these findings and demonstrate that MANF inhibits ER stress-induced cell death and caspase-3 activation in retinal cells and explants.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding is that there is likely a reciprocal regulation between p58 IPK and MANF in retinal cells undergoing ER stress. Recent studies show that MANF protects CNS neurons (Voutilainen et al, 2017 ) and markedly improves RGC survival in a rat glaucoma model (Gao et al, 2017 ). Our data support these findings and demonstrate that MANF inhibits ER stress-induced cell death and caspase-3 activation in retinal cells and explants.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of the unilateral striatal 6‐OHDA model, however, are that it replicates the degeneration of the nigrostriatal tract and this effect is quite reproducible and well‐tolerated by the animals (Penttinen et al., ). The effects on locomotion can also be quantified reliably so it is very useful in screening for new therapeutics aimed at restoring or protecting the mesencephalic dopamine system (Penttinen, Parkkinen, Voutilainen, et al., ; Voutilainen et al., ). Behavioral assessment is much easier with regards to locomotor activity and the use of the contralateral side as a control enables reliable and physiologically relevant comparison in biochemical assessment of the lesion (Ungerstedt & Arbuthnott, ).…”
Section: Neurotoxin‐induced Modelsmentioning
confidence: 99%
“…These include the other members of the GDNF family, neurturin ( Horger et al, 1998 ), artemin ( Baloh et al, 1998 ) and persephin ( Milbrandt et al, 1998 ), VEGF proteins ( Piltonen et al, 2011 ), PDGF ( Pietz et al, 1996 ), PACAP ( Takei et al, 1998 ), members of TGFβ superfamily, including TGFβ 1, 2 and 3 ( Krieglstein et al, 1995a ), GDF5 ( Krieglstein et al, 1995b ) and GDF15 ( Strelau et al, 2000 ), FGF20 ( Ohmachi et al, 2003 ) and two more recently identified related factors CDNF and MANF ( Lindholm et al, 2007 , Petrova et al, 2003 ). Many of these factors have been reported to be protective for nigrostriatal neurons in animal models of Parkinson's Disease, including GDNF, neurturin, CDNF, MANF, PDGF, FGF20 and PACAP ( Lindholm et al, 2016 , Voutilainen et al, 2017 ). However, no obvious abnormal midbrain dopaminergic neuron phenotype has been reported in mice that lack any of these factors ( Lindahl et al, 2017 ), and where an abnormal phenotype was initially reported in mice with a conditional deletion of Gdnf in the striatum ( Pascual et al, 2008 ), comprehensive analysis of multiple mouse lines failed to find any abnormal dopaminergic phenotype ( Kopra et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%